2013
DOI: 10.1111/bju.12027
|View full text |Cite
|
Sign up to set email alerts
|

Prostate volume in male patients with spinal cord injury: a question of nerves?

Abstract: Objective• To assess the influence of standardized complete surgical deafferentation of the lower urinary tract by sacral deafferentation (SDAF) and sacral anterior root stimulation (SARS) on prostate volume in men with spinal cord injury (SCI). Patients and Methods• In a prospective study, the prostate volume of men with SCI who underwent SDAF/SARS was measured using transrectal ultrasonography.• The prostate volumes of these men were compared with those of men with complete SCI but who did not undergo SDAF/S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 21 publications
1
3
0
Order By: Relevance
“…We observed a reduction in prostate mass in rodents receiving SCI, which is similar to that which occurs in men after SCI 49 and may be related to the high prevalence of hypogonadism within this population. 40 In an attempt to limit androgeninduced prostate enlargement, we administered TE in a low-dose (that has previously been reported to restore sex-organ weight and normal sexual and nonsexual behavior in chemically castrated rats).…”
Section: Mechanisms Of Testosterone Actionsupporting
confidence: 73%
“…We observed a reduction in prostate mass in rodents receiving SCI, which is similar to that which occurs in men after SCI 49 and may be related to the high prevalence of hypogonadism within this population. 40 In an attempt to limit androgeninduced prostate enlargement, we administered TE in a low-dose (that has previously been reported to restore sex-organ weight and normal sexual and nonsexual behavior in chemically castrated rats).…”
Section: Mechanisms Of Testosterone Actionsupporting
confidence: 73%
“…Studies in rats have shown that denervation of the prostate leads to almost complete loss of epithelium (14), indicating a strong trophic effect of nerves on normal prostate epithelium. Similarly, men with complete spinal cord injury had significantly smaller prostates than controls(15). Studies by Magnon et al(16) have shown that chemical or surgical ablation of nerves inhibits tumorigenesis and metastasis in both xenograft and transgenic mouse models of PCa, unequivocally establishing that nerve-PCa cell interactions play a significant role in PCa initiation and progression but the molecular basis of these interactions is still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Brasso et al reported that SP concentrations of KLK3 were significantly lower in SCI patients with lesions below T7 compared with patients with lesions at or above this level (52). Studies have shown that the prostate gland is smaller in men with SCI compared with healthy, noninjured men, and that this effect may be because of a prolonged central (rather than peripheral) desinnervation of the prostate gland (55). However, further pathophysiological studies of the prostate gland are necessary to investigate how a neurological trauma influences glandular function.…”
Section: Qualitative Map Of the Human Seminal Plasma Proteome-mentioning
confidence: 99%